2017
DOI: 10.1038/s41535-016-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Selection rules for Cooper pairing in two-dimensional interfaces and sheets

Abstract: Thin sheets deposited on a substrate and interfaces of correlated materials offer a plethora of routes towards the realization of exotic phases of matter. In these systems, inversion symmetry is broken which strongly affects the properties of possible instabilities -in particular in the superconducting channel. By combining symmetry and energetic arguments, we derive general and experimentally accessible selection rules for Cooper instabilities in noncentrosymmetric systems, which yield necessary and sufficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…The 2DES at the (111)LAO/STO interface [11] is an interesting subject of investigation, combining a polar discontinuity at the interface with such a hexagonal lattice. Signatures of the sixfold symmetry related to the (111)STO orientation have recently been observed by angle-resolved photoemission spectroscopy (ARPES) [12,13] and magnetoresistance [14,15] measurements, making the system potentially suitable for exotic time-reversal symmetry breaking superconductivity [16]. Moreover, ARPES measurements at the surface of (111)STO have confirmed a distinct orbital ordering of the t 2g manifold [12], where all the bands are degenerate at the point.…”
mentioning
confidence: 75%
“…The 2DES at the (111)LAO/STO interface [11] is an interesting subject of investigation, combining a polar discontinuity at the interface with such a hexagonal lattice. Signatures of the sixfold symmetry related to the (111)STO orientation have recently been observed by angle-resolved photoemission spectroscopy (ARPES) [12,13] and magnetoresistance [14,15] measurements, making the system potentially suitable for exotic time-reversal symmetry breaking superconductivity [16]. Moreover, ARPES measurements at the surface of (111)STO have confirmed a distinct orbital ordering of the t 2g manifold [12], where all the bands are degenerate at the point.…”
mentioning
confidence: 75%
“…This configuration has been likened to a strongly correlated analogue of graphene, and has been predicted to exhibit topological properties, unconventional superconductivity, as well as nematic phases. [14][15][16] Electric transport measurements have shown that the (111) LAO/STO interface exhibits many of the properties already seen in (001) LAO/STO, including a coexistence of superconductivity and magnetism. [17][18][19][20] However, the feature that distinguishes the (111) interface from the (001) interface is the strong anisotropy with respect to surface crystal direc-arXiv:1708.04809v2 [cond-mat.str-el] 28 Aug 2017 tion seen in almost all properties, including conductivity, Hall effect, superconductivity, quantum capacitance and longitudinal magnetoresistance.…”
mentioning
confidence: 97%
“…This configuration has been likened to a strongly correlated analogue of graphene, and has been predicted to exhibit topological properties, unconventional superconductivity, as well as nematic phases. [14][15][16] Electric transport measurements have shown that the (111) LAO/STO interface exhibits many of the properties already seen in (001) LAO/STO, including a coexistence of superconductivity R⊡ (kΩ) 0 5 10 15 20 Vg (V) 40 50 60 70 80 90 100 [112] [110] Ti 1 Ti 2 Ti3 O [110] [112] [ 1 1 1 ] [110] (a) (b) I VL VH VL VH [112] [110] I T=4.4K [112] FIG. 1. a) Schematic representation of the first three monolayers at the LAO/STO interface with the [112] and [110] labeled.…”
mentioning
confidence: 99%
“…It is thought that carriers flow in the two-dimensional (Fe 2+ As 3-) layers, while impurity doping to the (La 3+ O 2-) layer transfers the carriers generated in the (La 3+ O 2-) layer to the (Fe 2+ As 3-) layers etc [3]. Till now the major theoretical effort has been focused on the search for mechanism responsible for the pair formation in two-dimensions followed by inter-layer pair tunneling [2][3][4][5][6][7][8][9][10][11][12][13][14]. Sachdev et al [2] used large-N expansion to study finite temperature pairing fluctuations in 2D.…”
Section: Introductionmentioning
confidence: 99%
“…Sommer et al [12] described the evolution of fermion pairing in the dimensional crossover from threedimensional to two-dimensional as a strongly interacting Fermi gas of 6 Li atoms becomes confined to a stack of two-dimensional layers formed by a one-dimensional optical lattice. Recently, Scheurer et al [13] describes selection rules for Cooper pairing in two-dimensional interfaces and sheets of Sr 2 RuO4, LaAlO 3 /SrTiO 3 heterostructures, URu 2 Si 2 and UPt 3 as well as for single-layer FeSe. In these systems, time-reversal-symmetry is broken which strongly affects the properties of possible instabilities in particular in the superconducting channel.…”
Section: Introductionmentioning
confidence: 99%